2018
DOI: 10.3390/md16090338
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Highly N-Methylated Peptides Carmabin A and Dragomabin

Abstract: The first total synthesis of carmabin A and dragomabin was achieved at 52.3 mg and 43.8 mg scale, respectively. The synthesis led to determination of the configuration of carmabin A and reassignment of the configuration of dragomabin at the stereogenic centre on the alkyne-bearing fragment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…144 The absolute stereochemistry at C-35 and C-37 of 314 and 315 were revised and assigned by total synthesis. 145 Gallinamide A (317) (other name: sympostatin 4), a depsipeptide was isolated from a Schizothrix species of cyanobacteria. 146,147 Its stereostructure assignment of the Nterminal isoleucine residue was determined by total synthesis.…”
Section: Peptidementioning
confidence: 99%
“…144 The absolute stereochemistry at C-35 and C-37 of 314 and 315 were revised and assigned by total synthesis. 145 Gallinamide A (317) (other name: sympostatin 4), a depsipeptide was isolated from a Schizothrix species of cyanobacteria. 146,147 Its stereostructure assignment of the Nterminal isoleucine residue was determined by total synthesis.…”
Section: Peptidementioning
confidence: 99%
“… 100 Additionally, 50 was found to exhibit a better differential toxicity between parasite and mammalian cells (IC 50 = 182.3 μM) hypothesized to be caused by the removal of three carbons in the aliphatic chain. Total synthesis of 49 and 50 was carried out by Ye et al in 2018 101 and synthesis of 51 was completed by Chen et al in 2005. 102 …”
Section: Antipathogenic Natural Productsmentioning
confidence: 99%
“…In contrast, mabuniamide 9 has a longer peptide chain. Total synthesis and structure−activity relationship (SAR) studies of gallinamide A 4 and total synthesis of dragomabin 6 have previously been reported. Because isolation of enough amounts of biologically active molecules from marine cyanobacteria is difficult, the development of a practical chemical synthesis of ikoamide ( 1) is crucial for further pharmaceutical development and exploration of its structure−activity relationship.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Its unique structure and biological activity have received attention from scientists in parasitology. Several antimalarial peptides have been discovered from marine cyanobacteria, including hoshinoamide A, gallinamide A, , dragomabin, , venturamide A, companeramide A, and mabuniamide . These lipopeptides, which have unusual fatty acid chains, also exhibit different peptide lengths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation